Effects of environmental hypoxia and hypercarbia on ventilation and gas exchange in Testudines - Trevizan-Bau, Pedro; Abe, Augusto S. [UNESP]; Klein, Wilfried (Peerj Inc, 2018)
Background. Ventilatory parameters have been investigated in several species of Testudines, but few species have had their ventilatory pattern fully characterized by presenting all variables necessary to understand changes in breathing pattern seen under varying environmental conditions. Methods. We measured ventilation and gas exchange at 25 degrees C in the semi-aquatic turtle Trachemys scripta and the terrestrial tortoise Chelonoidis carbonarius under normoxia, hypoxia, and hypercarbia and furthermore compiled respiratory data of testudine species from the literature to analyze the relative changes in each variable. Results. During normoxia both species studied showed an episodic breathing pattern with two to three breaths per episode, but the non-ventilatory periods (T-NVP) were three to four times longer in T. scripta than in C. carbonarius. Hypoxia and hypercarbia significantly increased ventilation in both species and decreased T-NVP and oxygen consumption in T. scripta but not in C. carbonarius. Discussion. Contrary to expectations, the breathing pattern in C. carbonarius did show considerable non-ventilatory periods with more than one breath per breathing episode, and the breathing pattern in T. scripta was found to diverge significantly from predictions based on mechanical analyses of the respiratory system. A quantitative analysis of the literature showed that relative changes in the ventilatory patterns of chelonians in response to hypoxia and hyperbarbia were qualitatively similar among species, although there were variations in the magnitude of change.
Keywords: Reptilia; Normoxia; Breathing pattern; Breathing mechanics; Oxygen consumption